EFL LEARNERS’ POST-EDITING ON GOOGLR ENGLISH-INDONESIAN TRANSLATION OUTPUT - Bella Anggrina; Kripa Ellan Pramudita; Suparmi Suparmi (Universitas Negeri Padang, 2017)
Machine Translation (MT) helps people in translating one language into another language automatically without human intervention. One of MT is Google Translate which use for language learners to get information and to access new knowledge in another language. However, GT has some limitations in translation. It produces less accurate meaning and many errors occurred in its output. To achieve high-quality output, EFL learners use post-editing in revising translations output that have been produced by a machine translation (MT) system. There are two levels of Post-editing, namely light and full-post editing. In this study, the researchers investigated how the EFL learners used post-editing on Google English-Indonesian translation output. The item of the instrument was translation test. The test used in this study was Google English-Indonesian translation output. The participants of this study consisted of 20 graduate students of English Department of Universitas Negeri Padang who are taking translation subject. The data were gathered by using translation test. Then, the data were analyzed qualitatively. The result showed that both levels are used by the learners. In light post-editing, the learners modified lexical and syntax categories by replacing and adding the words. Meanwhile, in full post-editing technique, the students not only modified lexical and syntax categories, but also used appropriate style, fluency, and maintain the perfect faithfulness of the source text.